Effectiveness of Guided Inquiry Learning Models Viewed From Physics Learning Achievements - Syamsudin Amir; Dewi Hikmah Marisda (Berkala Ilmiah Pendidikan Fisika, 2021)
This study aimed to analyze the improvement in physics learning outcomes of XI MIA State Madrasah Aliyah 2 students in East Flores after being taught using the Guided Inquiry Learning model. The type of research was a pre-experimental design with one group Pretest – Post-test. The sample in this study was saturated, namely all students of class XI MIA MAN 2 Flores. The research instrument used was a learning achievement test consisting of 30 items in multiple-choice, validated by two experts. The data obtained was then analyzed in a quantitative descriptive manner for the increased learning achievement using the N-gain test. The results showed an increase in student learning achievement, as seen from the acquisition of physics learning outcomes after the guided inquiry learning was applied. Based on the N-gain value, students’ physics learning achievement was in the medium category. Also, the acquisition of student learning outcomes has increased after the guided inquiry learning model was applied--The results of this study expected to be one of the solutions in learning physics.